Modern organoaluminum reagents : preparation, structure, reactivity and use - Dagorne, Samuel; Woodward, Simon (Topics in Organometallic Chemistry, 2013)
Janusz Lewiński and Andrew E. H. Wheatley: Simple trivalent organoaluminum species: perspectives on structure, bonding and reactivity.- Stephan Schulz: Organoaluminum complexes with bonds to s-block, p-block, d-block, and f-block metal centers.- Samuel Dagorne and Christophe Fliedel: Low valent organoaluminium (+I, +II) species.- Rudolf Wehmschulte: Organoaluminum species in homogeneous polymerization catalysis.- Paul Knochel, Tobias Blümke, Klaus Groll and Yi-Hung Chen: Preparation of Organoalanes for Organic Synthesis.-  Yuki Naganawa and Keiji Maruoka: Reactions Triggered by Lewis Acidic Organoaluminum Species.- Usein M. Dzhemilev and Vladimir A. D'yakonov: Hydro-, Carbo- and Cycloalumination of Unsaturated Compounds.- Andreas Kolb and Paultheo von Zezschwitz: Organoaluminum Couplings to Carbonyls, Imines and Halides.- Oscar Pàmies and Montserrat Diéguez: Conjugate Addition of Organoaluminum Species to Michael Acceptors and Related Processes.